What Is the Evidence-Based Physiotherapy Level for Polarized Polychromatic Non-Coherent Light Applications? A Narrative Review - Taradaj, Jakub (Physiotherapy Review, 2021)
Despite many reports from basic research (in vitro, in vivo, and animal experiments), practitioners still have some doubts about the effectiveness and usefulness of polarized light in treating musculoskeletal disorders. It has even been widely accepted that the commercial use of these treatments is supported by a satisfactory level of scientific evidence based on reliable clinical articles. The main purpose of this paper is to present an original review of the literature on the subject in relation to the principles of evidence-based physiotherapy (EBP). This article comprises a critical review of relevant studies available in scientific databases, such as the Cochrane Library, Physiotherapy Evidence Database (PEDro), MEDLINE, and PubMed, along with an attempt to assess the methodological quality of these publications.